Long-term outcomes of combined optimized YAG-laser trabeculostomy and selective laser trabeculoplasty for primary open-angle glaucoma - A.S. Balalin; V.P. Fokin; S.V. Balalin; B.G. Dzhashi (РМЖ "Клиническая офтальмология")
A.S. Balalin, V.P. Fokin, S.V. Balalin, B.G. Dzhashi Volgograd Branch of the S. Fyodorov Eye Microsurgery Federal State Institution, Volgograd, Russian Federation Aim: to develop a combined technology of optimized YAG-laser trabeculostomy and selective laser trabeculoplasty and to evaluate its efficacy and safety in the treatment for primary open-angle glaucoma (POAG). Patients and Methods: this study enrolled three groups of patients. Group 1 (study group, prospective) included 87 patients (87 eyes) with early and moderate POAG before and after optimized YAG-laser trabeculostomy. Group 2 (control, prospective) included 78 patients (78 eyes) with early and moderate POAG before and after selective laser trabeculoplasty (SLT). Group 3 (control) included 60 healthy individuals (60 eyes). A technique to determine the topography of the collector channels and Schlemm's canal was developed to perform YAG-laser trabeculostomy. The location of the collector channels was determined with regard to Schlemm's canal using anterior segment optical coherence tomography (OCT). Patients were followed up after 1 day, 1, 6, 12, and 24 months. Results: after combined optimized YAG-laser trabeculostomy and SLT, a significant IOP-lowering effect (reduction in IOP level by 30.1%) was reported as early as day 1 after surgery. Meanwhile, after SLT, the maximum IOP-lowering effect (by 21.5%) was observed only 1 month after surgery. Over a year, a gradual decrease in the IOP-lowering effect (17.2%) was reported after SLT. After optimized YAG-laser trabeculostomy, the IOP-lowering effect was stable (by 30.1%) being 26.2% after 2 years. When comparing the percentage of IOP-lowering regimen, group 1 (after optimized YAG-laser trabeculostomy) patients used less combined medications (by 27.7%) than group 2 (after SLT) patients. Moreover, IOP-lowering therapy was canceled in 18.4% and 10.3% of patients, respectively. Conclusion: YAG-laser and OCT optimize trabeculostomy by providing an alternative non-invasive laser treatment for patients with early and advanced POAG. Optimized YAG-laser trabeculostomy along with SLT (in contrast to SLT alone) reduces IOP faster, provides a more significant and stable IOP-lowering effect, and allows the surgery to be performed in the projection of the collector channels more accurately using acceptable laser energy values. Keywords: glaucoma, trabeculostomy, selective laser trabeculoplasty, primary open angle glaucoma. For citation: Balalin A.S., Fokin V.P., Balalin S.V., Dzhashi B.G. Long-term outcomes of combined optimized YAG-laser trabeculostomy and selective laser trabeculoplasty for primary open-angle glaucoma. Russian Journal of Clinical Ophthalmology. 2023;23(4):181–191 (in Russ.). DOI: 10.32364/2311-7729-2023-23-4-2.